Pengendalian Bahan Baku Pada Bengkel Cat 66paintworks Dengan Menggunakan Metode EOQ (Economic Order Quantity), POQ (Periodic Order Quantity), Dan JIT (Just In Time) - Setyo, Alvitho Dwi; Widjanarko, Wirawan; Sumantyo, Franciscus Dwikotjo Sri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to compare the Economic Order Quantity (EOQ), Periodic Order Quantity (POQ), and Just In Time (JIT) methods in managing raw material inventory at 66paintworks Workshop. The primary issue lies in high total inventory costs due to the use of conventional forecasting methods. By calculating the Total Inventory Cost (TIC) for each method, the EOQ method was found to be the most optimal. The TIC using EOQ for paint is Rp1,403,760 and for clear coat is Rp1,403,820, significantly lower than POQ (paint: Rp16,450,860; clear: Rp16,450,688) and JIT (paint: Rp1,397,520; clear: Rp1,757,488). EOQ also provides more efficient ordering frequency while maintaining production continuity. Thus, the EOQ method is recommended as the most economical and stable inventory control strategy within this study context.